SEED CAKE OF JATROPHA CURCAS (L .), PO TENTIAL SUBSTRATE TO PRODUCE MAGGOTS AS FEED FOR REARED MONOGASTRIC ANIMALS - S. C. B. Pomalégni; D. S. J. C. Gbemavo; P. C. Gnanglè; S. R.Djossou; M. Kenis; S.Babatoundé; L. R Glèlè Kakai; G. A. Mensah Laboratory of Animal Science; Fishery; Veterinary ( LRZVH) / Sub-Programme of unconventional animal species (Journal of Animal and Plant Sciences, 2018)
Seeds of jatropha ( Jatropha curcas) are used worldwide to produce biodiesel and the oil extraction generates a high amount of waste called seed cake. Jatropha seed cake has high protein content but its valorization, for example as animal feed, is hampered by its toxicity and antinutritional properties. This study, carried out in Benin, West Africa, aimed to determine the capacity of jatropha seed cake to produce fly larvae for animal feed and assess the nutritional quality of the larvae. Three types of substrates were exposed to naturally occurring house flies: jatropha seed cake alone, the same seed cake enriched with earthworms to help detoxifying and decomposing the cake, and corn bran, a substrate commonly used in the region to produce fly larvae. All three substrates produced larvae of similar sizes. The yield obtained with corn bran was significantly higher (55.6 g per kg of dry substrate) than those with pure seed cake (44.5 g) and seed cake with earthworms (50.1 g) . However, the larvae produced with jatropha seed cake contained more proteins and other important nutrients than those produced with corn bran. These results show that jatropha seed cake can be valorized by producing fly larvae but it remains to be seen whether the fly larvae produced on jatropha seed cake are not toxic for animals. One solution could be to use jatropha seed cake
Keywords: biomass maggot; Maggots size; earthworms; substrate; chemical composition.